Different Measures of Auditory and Visual Stroop Interference and Their Relationship to Speech Intelligibility in Noise - Knight, Sarah; Heinrich, Antje (Frontiers in Psychology, 2017)
Inhibition – the ability to suppress goal-irrelevant information – is thought to be an important cognitive skill in many situations, including speech-in-noise (SiN) perception. One way to measure inhibition is by means of Stroop tasks, in which one stimulus dimension must be named while a second, more prepotent dimension is ignored. The to-be-ignored dimension may be relevant or irrelevant to the target dimension, and the inhibition measure – Stroop interference (SI) – is calculated as the reaction time difference between the relevant and irrelevant conditions. Both SiN perception and inhibition are suggested to worsen with age, yet attempts to connect age-related declines in these two abilities have produced mixed results. We suggest that the inconsistencies between studies may be due to methodological issues surrounding the use of Stroop tasks. First, the relationship between SI and SiN perception may differ depending on the modality of the Stroop task; second, the traditional SI measure may not account for generalized slowing or sensory declines, and thus may not provide a pure interference measure. We investigated both claims in a group of 50 older adults, who performed two Stroop tasks (visual and auditory) and two SiN perception tasks. For each Stroop task, we calculated interference scores using both the traditional difference measure and methods designed to address its various problems, and compared the ability of these different scoring methods to predict SiN performance, alone and in combination with hearing ability. Results from the two Stroop tasks were uncorrelated and had different relationships to SiN perception. Changing the scoring method altered the nature of the predictive relationship between Stroop scores and SiN perception, which was additionally influenced by hearing ability. These findings raise questions about the extent to which different Stroop tasks and/or scoring methods measure the same aspect of cognition. They also highlight the importance of considering additional variables such as hearing ability when analysing cognitive variables.